PENINGKATAN PENGUASAAN KOSAKATA DALAM KEMAMPUAN BERBICARA BAHASA INDONESIA MELALUI METODE BERCERITA SISWA KELAS III UPT SDN 100 GRESIK - Isnaini Jihan Safitri; Afakhrul Masub Bakhtiar (STKIP Subang, 2022)
Abstract This study aims to determine the effect of the storytelling learning method on the mastery of Indonesian vocabulary in class III UPT SDN 100 Gresik. This research is motivated by the low mastery of Indonesian vocabulary in class III UPT SDN 100 Gresik. This research is a descriptive classroom action research. The subjects in this study were 20 students in 1 class. The data collection technique in this study used an oral test. The data analysis technique used covariance analysis. The results showed that the significant value was evidenced by the calculated significance value in the hypothesis test of 0.060 which was greater than 0.05 with a partial value of 0.78 or 78%. In this case, it can be said that learning by using the storytelling method has a significant effect or it can be said that the learning of Indonesian vocabulary mastery increases from the results of the previous cycle data. Keywords : Storytelling Learning Method, Indonesian Vocabulary Mastery.